Gender Differences in the Neurobiology of Anxiety: Focus on Adult Hippocampal Neurogenesis - Alessandra Aparecida Marques; Mário Cesar do Nascimento Bevilaqua; Alberto Morais Pinto da Fonseca; Antonio Egidio Nardi; Sandrine Thuret; Gisele Pereira Dias (Neural Plasticity)
Although the literature reports a higher incidence of anxiety disorders in women, the majority of basic research has focused on male rodents, thus resulting in a lack of knowledge on the neurobiology of anxiety in females. Bridging this gap is crucial for the design of effective translational interventions in women. One of the key brain mechanisms likely to regulate anxious behavior is adult hippocampal neurogenesis (AHN). This review paper aims to discuss the evidence on the differences between male and female rodents with regard to anxiety-related behavior and physiology, with a special focus on AHN. The differences between male and female physiologies are greatly influenced by hormonal differences. Gonadal hormones and their fluctuations during the estrous cycle have often been identified as agents responsible for sexual dimorphism in behavior and AHN. During sexual maturity, hormone levels fluctuate cyclically in females more than in males, increasing the stress response and the susceptibility to anxiety. It is therefore of great importance that future research investigates anxiety and other neurophysiological aspects in the female model, so that results can be more accurately applicable to the female population.